Evaluasi Kinerja Sistem Drainase Menggunakan Metode Rasional Dan Persamaan Manning Pada Koridor Jalan Suluh – Jalan Pembangunan Iii Kota Medan - Simaremare, Yessika Angelina; Sihole, Arjuna; Simanjuntak, Rizky; Prayogo, Wisnu; Harahap, Rumilla (CV. SINAR HOWUHOWU, 2026)
This study aims to evaluate the performance of the drainage system in the Jalan Suluh – Jalan Pembangunan III corridor in Medan City based on surface runoff discharge. The main problem that occurs is waterlogging during high-intensity rainfall due to inadequate channel capacity. The methods used include rainfall analysis using the Log Pearson Type III distribution, rainfall intensity calculations using the Mononobe method, runoff discharge calculations using the rational method, and channel capacity analysis using the Manning equation. The data used were rainfall data for the 2016–2023 period and direct field measurements. The results showed that the maximum runoff discharge of 1.63 m³/second was greater than the capacity of most drainage channels. Of the eight segments analyzed, only one segment met capacity, while the other seven segments were unable to accommodate the flow discharge. Based on these results, it can be concluded that the drainage system at the study site is not functioning optimally and requires improvements in the form of channel normalization and redesign of channel dimensions.